On Certain New Subclass of Meromorphic Close-to-Convex Functions. (11th March 2013) - Yi, Jing-Ping; Wang, Zhi-Gang; Zeng, Ming-Hua
Abstract : We introduce a certain new subclass of meromorphic close-to-convex functions. Such results as inclusion relationship, coefficient inequalities, distortion, and growth theorems for this class of functions are derived.